Morphology of unilateral rectus sternalis:A cadaveric study (International Journal of Biomedical Research, 2016)
The rectus sternalis is a rare anatomic variant muscle in the anterior chest wall. Knowledge of variations in the anterior chest wall musculature is important for operating surgeons as well as radiologists. Its overall incidence is 3-5% world wide. The present study was conducted on 30 cadavers in the department of anatomy, Osmania medical college to evaluate the incidence of rectus sternalis.We observed presence of unilateral rectus sternalis in adult male cadaver. The incidence of this variant muscle on the basis of our study is 3.3%.